Autoimmune diseases and HIV infection: A cross-sectional study. Issue 4 (January 2017) - Virot, Emilie; Duclos, Antoine; Adelaide, Leopold; Miailhes, Patrick; Hot, Arnaud; Ferry, Tristan; Seve, Pascal
Abstract : Abstract: To describe the clinical manifestations, treatments, prognosis, and prevalence of autoimmune diseases (ADs) in human immunodeficiency virus (HIV)-infected patients. All HIV-infected patients managed in the Infectious Diseases Department of the Lyon University Hospitals, France, between January 2003 and December 2013 and presenting an AD were retrospectively included. Thirty-six ADs were found among 5186 HIV-infected patients which represents a prevalence of 0.69% including immune thrombocytopenic purpura (n = 15), inflammatory myositis (IM) (n = 4), sarcoidosis (n = 4), Guillain–Barré syndrome (GBS) (n = 4), myasthenia gravis (n = 2), Graves' disease (n = 2), and 1 case of each following conditions: systemic lupus erythematosus, rheumatoid arthritis, autoimmune hepatitis, Hashimoto thyroiditis and autoimmune hemolytic anemia. One patient presented 2 ADs. Thirty patients were known to be HIV-infected when they developed an AD. The AD preceded HIV infection in 2 patients. GBS and HIV infection were diagnosed simultaneously in 3 cases. At AD diagnosis, CD4 T lymphocytes count were higher than 350/mm 3 in 63% of patients, between 200 and 350/mm 3 in 19% and less than 200/mm 3 in 19%. Twenty patients benefited from immunosuppressant treatments, with a good tolerance. ADs during HIV infection are uncommon in this large French cohort. Immune thrombocytopenic purpura, sarcoidosis, IM, and GBS appear to be more frequent than in the general population. Immunosuppressant treatments seem to be effective and well tolerated.